Performa Kualitas Telur Ikan Gabus (Channa striata blkr) Dengan Pemberian Pakan Berbeda Dalam Wadah Terkontrol - Yulainty Adipu; Ahmad Rovik (Gorontalo Fisheries Journal, 2018)
This study aims to determine the management techniques of snakehead fish in the spawning process conducted in a controlled container and to know the performance of egg quality of snakehead fish. The experimental method was done experimentally by using a complete randomized design (RAL) with three feeding treatments and three replications, the treatment consisted of treatment A using 38% artificial protein, B treatment using rucah (fresh fish), and C treatment using mascot . The test animal used is the snake head totaling 49 tail, with the size of weight 350 grams up to 800 grams. The variables observed in this research consist of fecundity, hatchability, survival rate and water quality. The feed treatment A (golden snail) resulted in the highest number of eggs (fecundity) 5928 grains, followed by treatment B (feed trash) that is 4360 grains, and treatment A (pellet feed) ie 4134 grains. The result of hatching rate analysis at the highest treatment A reached 92,10%, in treatment B hatching degree was obtained 71,42%, while at treatment C obtained 56,60%. The observation variable for seed survival rate in treatment A resulted in 4367 head, whereas at treatment B obtained larvae 2245 tail, and at treatment C obtained 1450 tail. Based on the results of the research I can conclude that with different did not give a real effect on the number of eggs, hatchability and survival rate in snake head. While for water quality measurement obtained temperature value around 27-320C, brightness 30 - 40 cm, oxygen and pH at normal value 7.Â Â Keywords : Quality eggs, snakehead fish, Feed